2016
DOI: 10.3747/pdi.2015.00090
|View full text |Cite
|
Sign up to set email alerts
|

The Trio Trial – a Randomized Controlled Clinical Trial Evaluating the Effect of a Biocompatible Peritoneal Dialysis Solution on Residual Renal Function

Abstract: ISRCTN26252543.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
20
0
3
Order By: Relevance
“…Modifying the peritoneal dialysate by raising pH, reducing glucose, and using non-lactate fluids as a buffer was thought to lessen the adverse effects of conventional PD solutions. Previous small, randomized controlled trials (RCTs) have demonstrated conflicting results with respect to the effects of biocompatible PD solutions on RRF decline in PD patients compared with conventional PD solutions [68][69][70][71][72] . Yohanna et al 73 systematically reviewed 11 trials in which 643 patients were included.…”
Section: Preservation Of Rrfmentioning
confidence: 99%
“…Modifying the peritoneal dialysate by raising pH, reducing glucose, and using non-lactate fluids as a buffer was thought to lessen the adverse effects of conventional PD solutions. Previous small, randomized controlled trials (RCTs) have demonstrated conflicting results with respect to the effects of biocompatible PD solutions on RRF decline in PD patients compared with conventional PD solutions [68][69][70][71][72] . Yohanna et al 73 systematically reviewed 11 trials in which 643 patients were included.…”
Section: Preservation Of Rrfmentioning
confidence: 99%
“…Most recently, the TRIO trial, designed to verify the results of balANZ, randomized 67 incident dialysis patients from two centers in Canada and one in Hong Kong to the lactate‐buffered NpHLGDP Gambrosol Trio (Gambro Lundia AB, Lund, Sweden), or conventional PD solutions, and chose as primary outcome slope of decline of RKF . Significantly lower rates in the decline of RKF and urine output were observed with NpHLGDP solution (decline of 0.132 vs. 0.174 ml/minute/1.73 m 2 /month with Gambrosol Trio and conventional PD solution, respectively, p = 0.001), concordant with the findings of previous studies.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…A Gambrosol Trio biokompatibilis PD-oldattal kétéves követés során -a konvencionális Dianeal oldatokkal kezelt csoporttal összevetve -kisebbnek találták [19] a residualis GFR csökkenésének ütemét (0,132 ml/perc/1,73 m 2 /hónap 51 biokompatibilis ágon szereplő és 0,174 ml/perc/1,73 m 2 /hónap a standard hagyományos ágon lévő 50 beteg esetében; p = 0,001).…”
Section: Biokompatibilis Peritonealis Dializálóoldatokunclassified